2021
DOI: 10.23887/jpbi.v9i2.32657
|View full text |Cite
|
Sign up to set email alerts
|

Teacher’s Ability in Preparing Lesson Plans for English as a Foreign Language During the Pandemic in the Senior High School

Abstract: There are still many students who do not follow online learning well. Students who are not focused on online learning. In addition, there are still many teachers who find it challenging to design appropriate learning for students. This will have an impact on learning activities that cannot run optimally, especially in English subjects. The negative impact of this is that the ability of students will decrease. This study aims to analyze the teacher's ability to prepare EFL lesson plans through Google Classroom,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Previous study explains that it is important because the teachers can imagine the teaching plan that has been designed in it which is also to improve the teaching process to become better implementation (Wulandari et al, 2021). Other study had a finding regarding the preparation of lesson plan by the teachers during the remote teaching process where they found that the preparation of lesson plan was ineffective because the teachers had a lack of stating and identifying the indicator of learning, selecting appropriate learning materials, learning methods, and learning platforms (Kusuma et al, 2021). The result found that in SMAN 2 Banjar, the teachers had already prepared their own lesson plan.…”
Section: Remote Teaching Implementationmentioning
confidence: 99%
“…Previous study explains that it is important because the teachers can imagine the teaching plan that has been designed in it which is also to improve the teaching process to become better implementation (Wulandari et al, 2021). Other study had a finding regarding the preparation of lesson plan by the teachers during the remote teaching process where they found that the preparation of lesson plan was ineffective because the teachers had a lack of stating and identifying the indicator of learning, selecting appropriate learning materials, learning methods, and learning platforms (Kusuma et al, 2021). The result found that in SMAN 2 Banjar, the teachers had already prepared their own lesson plan.…”
Section: Remote Teaching Implementationmentioning
confidence: 99%
“…Cognitive refers to people's thinking, problem-solving, and decision-making processes. For instance, behaviorists simply claim that the repetition of a response to a stimulus strengthens it (Maheswari & Dewi, 2023).…”
Section: Introductionmentioning
confidence: 99%